Shattered - Mancusi, Mari (Scorched, 2014)
"Trinity, Connor, and Caleb are holed up in Texas when Emmy, the baby dragon, is caught on tape and the video goes viral, sending them on the road again, following an old map leading to a man who has come from the future to help"--OCLC.